Campylobacteriosis and control strategies against Campylobacters in poultry farms - Zainol, Mohamad Fadzirul Anwar; Safiyanu, Mansur Bala; Abd Aziz, Saleha; Omar, Abdul Rahman; Chuang, Kuo Pin; Mariatulqabtiah, Abdul Razak (Korean Society for Microbiology and Biotechnology, 2024)
Campylobacteriosis is a significant foodborne illness caused by Campylobacter bacteria. It is one of the most common bacterial causes of gastroenteritis worldwide, with poultry being a major reservoir and source of infection in humans. In poultry farms, Campylobacters colonize the intestinal tract of chickens and contaminate meat during processing. Vaccines under development against Campylobacters in poultry showed partial or no protection against their cecal colonization. Therefore, this review will elaborate on campylobacteriosis and emphasize the control strategies and recent vaccine trials against Campylobacters in poultry farms. The epidemiology, diagnosis, and treatment of Campylobacter infection, along with specific mention of poultry Campylobacter contamination events in Malaysia, will also be discussed.